Aspectos ecotoxicológicos relacionados à carcinicultura marinha. - Aragão, Janisi Sales (2012)
Farming of shrimp is an important economic activity; however, its exponential growth has attracted attention to the potential impacts brought over the environment. Wastewater generated by this activity can contribute to the eutrophication of waters receiving these effluents, as those may bear a variety of contaminants, such as sodium metabisulfite, a sulphitant agent that removes the oxygen from water and food. Additionally, this effluent carries the phytoplankton community that proliferates in these systems, which may include toxic cyanobacteria. Therefore, the aim of the present study was to perform an ecotoxicological assessment using biological test models and biological responses to evaluate potential impacts caused by use of sodium metabisulfite and by the proliferation of cyanobacteria in shrimp farming. Phytoplankton samples were collected in three shrimp farms from the state of Ceará for quantitative and qualitative analysis and for the isolation of cyanobacteria. The microorganisms, which were identified by morphological and molecular techniques, were grown in laboratory to o btain organic extracts on which were conducted toxicity tests with mice and mysids. Sodium metabisulfite was evaluated through acutetoxicity tests using organisms at different trophic levels (microalgae, cladocerans, shrimps and fish) and by the rate of oxygen consumption and enzymatic activities (CAT,AChE and GST) in shrimps. On fish, tests evaluating the embriolarval development and enzymatic activities (AChE and GST) were performed. Qualitative and quantitative analysis of phytoplankton community showed a large number of species from nearly all classes of phytoplankton, including cyanobacteria. From this latter group, Synechococcus sp. was isolated and cultivated, and the extract generated from the living cells showed toxicity in mice, as evidenced by damage to the liver and kidneys of animals. For acute toxicity tests sodium metabisulphite showed an EC 50 of 24.29 mg/L for the microalgae and LC 50 of 34.90 mg/L and 69.65 mg/L for cladocer ans and shrimp, respectively. Regarding the consumption of oxygen and enzymatic activities, these did not show significant differences when compared to their respective controls, except for the AChE in shrimp and GST in fish. On embriolarval developing of fish, sodium metabisulfite caused different types of effects, from destruction of eggs to deformities in larvae. Thus, these results show that sodium metabisulphite and the cyanobacteria Synechococcus sp. are toxic to other organisms, evidenced by both, acute and chronic toxicity